PORTABLE STABILIZER FOR PICO-SCALE BUOY GENERATOR - Mohamed Salleh, Putra Ahmad Khalifa (IRC, 2016)
As the world progresses, the amount of electricity consumption is increasing and the non-renewable resources that are currently being used to generate electricity are converging to a depletion state. One of the solutions to overcome this issue is to use and utilize the renewable energy. This report focuses on wave energy since it has the highest potential to generate electricity as compared to other renewable resources. Wave energy has no uniform frequency and amplitude causing a generator, specifically Wave Energy Converter (WEC) to generate an unstable or unclean electrical energy. Furthermore, the scale of the existing technologies are all robust and designed to stabilize a large amount of unstable electricity and there is no small scale stabilizer to be used for pico-scale generator (<5kW). There are few methods used in the existing technologies to stabilize the unstable electrical signal. They are Partial-Scale Frequency Converter, Full-Scale Frequency Converter, Diode Rectifier, Pure AC Converter, DC/AC Converter, Pure DC Converter, etc. All of these technologies are consist of numbers of sub converters such as AC-DC converter, DC-AC converter, and the combination of these two to stabilize the unstable electrical signal.